Mysticism Without Bounds: Perception of Space - Chakravorty, Meera (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
The idea of silence as experience and timely is unique because silence is healing and is essential for the time in which we live. The life and facts as lived by the vachana mystics and expressed in their songs and writings can help people of today dive deeper into their life’s mission. This expression of self-mystification has marked the different and distinctive angle of our symbolic world, i.e., its mystical space, and has promoted some concrete movements aimed at transformasion in the life’s mission of the people. Before being intellectual and cultural, the revolution might have been mystical thanks to the vachana mystics who are able to provoke discussions and debates about important issues in human’s life by broadening the life’s canvas and calling the devotees to cross the boundaries of space and time. In turn, we will be led towards the writing of the history of silence as the liberating perception of space.